September 5 [videorecording (DVD)] - Fehlbaum, Tim, 1982-; Binder, Moritz; David, Alex (Screenwriter); Sarsgaard, Peter; Magaro, John, 1983-; Chaplin, Ben; Benesch, Leonie, 1991-; Förderer, Markus, 1983-; Dangel, Lorenz (Paramount, 2025)
September 5 unveils the decisive moment that forever changed media coverage and continues to impact live news today. Set during the 1972 Munich Summer Olympics, the film follows an American sports broadcasting team that quickly adapted from sports reporting to live coverage of the Israeli athletes taken hostage. Through this lens, September 5 provides a powerful new perspective on the live broadcast seen globally by an estimated one billion people at the time.